+0  
 
0
38
1
avatar

Solve 3a + 4b = 5a - 6b + 24 - 3a for a in terms of b.

 Jul 19, 2023
 #1
avatar+8 
0

You need to isolate a on one side of the equation and b on the other side. 

3a+4b=5a−6b+24−3a
Combine 5a and -3a to get 2a.
3a+4b=2a−6b+24
Subtract 2a from both sides of the equation.
3a+4b−2a=−6b+24
Combine 3a and −2a to get a.
a+4b=−6b+24
Subtract 4b from both sides of the equation.
a=−6b+24−4b
Combine -6b and -4b to get -10b.
a=−10b+24

Therefore, the solution is a = 24 – 10b

 Jul 23, 2023

2 Online Users

avatar
avatar